Analisis Daya Dukung Lingkungan Berbasis Jasa Lingkungan Penyediaan Pangan Dan Air di Kawasan Perkotaan Lapai - Muhmmad Arfandi; La Ode Safuan; Iskandar Iskandar (Jurnal Perencanaan Wilayah, 2022)
The carrying capacity of the regional environment is a study that needs to be considered in spatial planning of city area.  The purpose of this paper is to determine characteristics ecoregion, distribution of environmental service index, and status of environmental carrying capacity on providing food and water supply, in planning development plan urban area of Lapai.  The method used is a spatial and tabular analysis using a geographic information system on the characteristics of ecoregion, environmental service index and status of the carrying capacity of environment for providing food and water.  The results of this study are the characteristics of ecoregions that play a role in determining the environmental service index of food and water supply are landscapes, natural vegetation and land cover.  The status of the carrying capacity of food supply in Lapai urban area is still in surplus, with details of 166.733 Ha or 58.24% not having crossed the threshold of need, and 119.5409 Ha or 41.76% having crossed the threshold. The status of the carrying capacity of water supply throughout the entire region is still in surplus.Keywords: carrying capacity, environmental services, food, clean water